DEVELOPMENT AND EVALUATION OF OFLOXACIN FLOATING TABLETS USING NATURAL POLYMER: STERCULIA FOETIDA LINN. GUM - Gulkari, Vijay D.; Bakhle, Suparna S.; Yelane, Leena S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The aim of the present work was to develop a gastro retentive drug delivery system of Ofloxacin with the objective of retarding the drug release when the dosage form is exposed to gastrointestinal fluid. Methods: Floating tablets of Ofloxacin were developed using a natural gum like Sterculia foetida. The prepared tablets were evaluated in terms of their precompression parameters, physical characteristics, in vitro buoyancy, in vitro drug release and release order kinetics. The formulations were optimized for different concentrations of Sterculia foetida. Results: The results of in vitro release studies showed that optimized formulation (F4) could sustain drug release (97.86%) for 24 h and remain buoyant for 24 h. The optimized formulation was subjected to various release kinetic investigations and it was found that the mechanism of drug release was predominantly diffusion with a minor contribution from polymeric relaxation. Conclusion: Floating tablets of Ofloxacin were successfully formulated with the ability of providing controlled release and non-Fickian transport of the drug from tablets was confirmed. Keywords: Ofloxacin, Floating drug delivery system, Sterculia foetida, Buoyancy